School Supervisor Competence in Assessing Performance Principal of Junior High School Level - Liza Liza; Erny Roesminingsih; Nunuk Hariyati (IJORER : International Journal of Recent Educational Research, 2024)
Objective: This study aims to describe and analyze data on the competence of school supervisors in carrying out school principals' performance assessments to create effective education units (Phenomenological Study in Sidoarjo). Method: This research uses a qualitative approach with the research subject, namely the Sidoarjo Regency Education Service supervisor at the Junior High School Level. The data collection technique in this research uses three data collection techniques, namely participant observation, in-depth interviews, and study of documents. Results: The assessment results show that the performance of school principals is critical in realizing an effective school. The school supervisor oversees the school principal's performance appraisal process. They start from collecting, processing, analyzing, and interpreting data about the quality of the school principal's work according to his duties as a school principal. School supervisors conduct managerial supervision to correct weaknesses in target schools through intensive training. School supervisors are one of the parts that are very influential in improving the quality of education in target schools. School supervisors always try to improve the ability of school management personnel in all aspects in order to obtain optimal quality education. Novelty: This study shows five competencies of school supervisors in carrying out performance assessments of school principals, namely personality, managerial supervision, academic supervision, educational evaluation, research and development, and social competence.